Risk factors based vessel-specific prediction for stages of coronary artery disease using Bayesian quantile regression machine learning method - Park, Hyung Bok (2023)
Funding Information: This work was supported by the Korea Medical Device Development Fund grant funded by the Korean government (Ministry of Science and ICT; Ministry of Trade, Industry and Energy; Ministry of Health & Welfare, Republic of Korea; and Ministry of Food and Drug Safety; Project Number: 202016B02) and funded in part by a generous gift from the Dalio Institute of Cardiovascular Imaging and the Michael Wolk Foundation. This work was also supported by the National Research Foundation of Korea [RS‐2022‐00165404, 2022R1A5A6000840, 2020R1I1A1A01073151]. The funder of the study had no role in study design, data collection, data analysis, data interpretation, or writing of the report. Publisher Copyright: © 2023 The Authors. Clinical Cardiology published by Wiley Periodicals, LLC.